Multinationals, SMEs and Non-Profit Organisations participating in the UN Global Compact - Carby-Hall, Jo (Lex Social: Revista de Derechos Sociales, 2020)
This paper attempts to illustrate the importance of the UN Global compact concept by examining its history and features, analysing its weaknesses and criticisms, evaluating its strengths and asking if its continuance is desirable globally. In the summing up part of the paper the conclusion is reached that the continuance of the Global Compact is essential.